2020
DOI: 10.3389/fphar.2020.00434
|View full text |Cite
|
Sign up to set email alerts
|

Spadin Selectively Antagonizes Arachidonic Acid Activation of TREK-1 Channels

Abstract: TREK-1 channel activity is a critical regulator of neuronal, cardiac, and smooth muscle physiology and pathology. The antidepressant peptide, spadin, has been proposed to be a TREK-1-specific blocker. Here we sought to examine the mechanism of action underlying spadin inhibition of TREK-1 channels. Heterologous expression in Xenopus laevis oocytes and electrophysiological analysis using two-electrode voltage clamp in standard bath solutions was used to characterize the pharmacological profile of wild-type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…In several previous lines of studies, spadin was shown to reduce the current mediated by TREK-1 in heterologous systems [ 27 , 43 , 44 ]. Both human and mouse TREK-1 channels are inhibited by spadin at low concentrations [ 27 , 43 , 44 ]. However, these studies show that the effect of spadin on TREK-1 activity is enhanced by arachidonic acid (AA), but spadin effect on basal activity of such channels is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In several previous lines of studies, spadin was shown to reduce the current mediated by TREK-1 in heterologous systems [ 27 , 43 , 44 ]. Both human and mouse TREK-1 channels are inhibited by spadin at low concentrations [ 27 , 43 , 44 ]. However, these studies show that the effect of spadin on TREK-1 activity is enhanced by arachidonic acid (AA), but spadin effect on basal activity of such channels is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the treprostinil inhibited current was greater than the original baseline starting current, pre-BL-1249 treatment. BL-1249 pre-activation of TREK-1 current has been shown to antagonize the effect of the inhibitor, spadin ( Ma and Lewis, 2020 ), a similar effect to that observed for TREK-2 current with the activator ML335 and inhibitor norfluoxetine ( Lolicato et al, 2017 ; Proks et al, 2020 ).…”
Section: Discussionmentioning
confidence: 70%
“…To try and elucidate further how treprostinil might be conferring its inhibitory effects on the TREK channels, we considered a known gain-of-function (GOF) mutation that affects the gating of the channel (Y284A). This amino acid has previously been shown to attenuate the effect of the activator, flufenamic acid (FFA) and the effect of arachidonic acid ( Veale et al, 2014 ; Ma and Lewis, 2020 ) and antagonize the inhibitory effects of norfluoxetine and spadin ( McClenaghan et al, 2016 ; Ma and Lewis, 2020 ). As previously reported ( Veale et al, 2014 ) mutation of Y284 to an alanine in TREK-1, resulted in channels with large outward currents of 95.8 pA pF −1 (95% CI: 74.6 to 117.0, n = 5) which were significantly larger ( p < 0.05, unpaired t -test) than WT TREK-1, 24.2 pA pF −1 (95% CI: 18.3 to 30.1, n = 8) and in agreement with channels having a higher P o ( Proks et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we applied spadin as a selective antagonist of TREK‐1 channels to test whether TREK‐1 channels are the target of quercetin. Spadin is an engineered fragment of the natural NTSR3/sortilin propeptide and has been shown to inhibit TREK‐1 channel currents only when pre‐activated with arachidonic acid, but not by BL‐1249 or by CDC (Ma & Lewis, 2020). Given that we observed clear inhibition by spadin of activation by quercetin, the flavonoid presumably shared some mechanisms of action with arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%